2017
DOI: 10.1007/s00406-017-0832-8
|View full text |Cite
|
Sign up to set email alerts
|

Scary symptoms? Functional magnetic resonance imaging evidence for symptom interpretation bias in pathological health anxiety

Abstract: Patients with pathological health anxiety (PHA) tend to automatically interpret bodily sensations as sign of a severe illness. To elucidate the neural correlates of this cognitive bias, we applied an functional magnetic resonance imaging adaption of a body-symptom implicit association test with symptom words in patients with PHA (n = 32) in comparison to patients with depression (n = 29) and healthy participants (n = 35). On the behavioral level, patients with PHA did not significantly differ from the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…These blocks were associated with greater recruitment of frontoparietal regions implicated in the task-based network and in executive control, left-lateralized semantic/linguistic processing (e.g., Broca’s area), and visual processing (Figure 2; Table 4). Consistent with the theoretical foundation for the IAT, and convergent with a few smaller neuroimaging IAT studies in nondepressed samples (Ballard et al, 2019; Egenolf et al, 2013; Mier et al, 2016; Yan et al, 2019), this neural pattern suggests behavioral responses during negative = me/positive = not me blocks produced an increased neural demand for response conflict resolution and/or elaborative semantic processing. Such neural patterns would be predicted when mental associations between two constructs (“me” and negative items) are relatively loose, less automated, or less prepotent.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These blocks were associated with greater recruitment of frontoparietal regions implicated in the task-based network and in executive control, left-lateralized semantic/linguistic processing (e.g., Broca’s area), and visual processing (Figure 2; Table 4). Consistent with the theoretical foundation for the IAT, and convergent with a few smaller neuroimaging IAT studies in nondepressed samples (Ballard et al, 2019; Egenolf et al, 2013; Mier et al, 2016; Yan et al, 2019), this neural pattern suggests behavioral responses during negative = me/positive = not me blocks produced an increased neural demand for response conflict resolution and/or elaborative semantic processing. Such neural patterns would be predicted when mental associations between two constructs (“me” and negative items) are relatively loose, less automated, or less prepotent.…”
Section: Discussionsupporting
confidence: 80%
“…Both neuroimaging and computational modeling techniques have the potential to reveal unique insights regarding the component neurocognitive processes that contribute to behavioral performance patterns on the task, providing insights into the nature of the task as well as potential brain-based, neurocomputational treatment targets. A few small neuroimaging IAT studies have been conducted to date, including studies of implicit self-associations conducted in healthy samples (Ballard et al, 2019; Egenolf et al, 2013) and studies of associations between harm and bodily symptoms in patients with and without health anxiety (Mier et al, 2016; Yan et al, 2019). Findings collectively suggest that during “incongruent” IAT blocks (i.e., when behavioral responses are routinely slowed due to “incongruent” key-mapping pairings), this is associated with an increased neural demand for cognitive control and executive or “task”-relevant networks.…”
mentioning
confidence: 99%
“…This cerebral region is part of the prefrontal-parietal network [ 7 ] associated with sensory information, in which response-relevant information from the top-down promotes flexible, goal-directed behavior [ 59 ]. Studies in healthy controls and individuals with pathological health anxiety have revealed that a hyper-activated parietal cortex is implicated in implicit emotional processing [ 60 , 61 ]. As the prefrontal cortex and parietal cortex are the two important parts of frontoparietal network involving in implicit cognitive reappraisal [ 23 ], the increased activity of parietal cortex may be a compensatory mechanism for reduced recruitment of dlPFC and dmPFC during implicit reappraisal.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the notion that stronger associations cause longer reaction times (RTs) and require more cognitive control during the incongruent than congruent pairings (Greenwald et al ., 1998), the extent of automatic associations of in-ethnicity and in-team members can be easily investigated. Previous studies revealed that, by comparing the incongruent and congruent pairings, higher activation in the dorsolateral prefrontal cortex (DLPFC) and posterior parietal cortex (PPC) are apparent indicators of stronger implicit associations (Fedorenko et al ., 2013; Yan et al ., 2019). However, to our knowledge, this approach has not been used to investigate differences in strength of associations in the in-ethnicity vs in-team bias.…”
Section: Introductionmentioning
confidence: 99%